Understanding the local energy transitions process: a systematic review - Selvakkumaran, Sujeetha; Ahlgren, Erik O. (International Journal of Sustainable Energy Planning and Management, 2018)
The objective of this paper is to better understand the local energy transitions process, given the importance of local energy transitions. A systematic literature search was conducted and 18 core and 18 peripheral papers on local energy transitions were selected. The 18 core papers were assessed using the framework given by Turnheim et. al. [1]. Findings show that local energy transitions have characteristics or features which are not adequately explained by the framework used. Sources of innovation and the innovation in niches in local energy transitions are explained by socio-technical theories such as Strategic Niche Management (SNM) and Multi-Level Perspective (MLP). The pathway dynamics and the normative goals are covered by quantitative modeling studies of local energy transitions. The specific features of local energy transitions which are not adequately analysed by the existing framework are ownerships of transitions, situative governance issues, spatial scale issues, differing priorities and differing institutional structures, along with the analysis of pathway dynamics. A suggestion for extending a framework to analyse local energy transitions is proposed.